SYNERGISTIC ANTIOSTEOPOROTIC EFFECT OF LEPIDIUM SATIVUM AND ALENDRONATE IN GLUCOCORTICOID-INDUCED OSTEOPOROSIS IN WISTAR RATS - Elshal, Mohamed F; Almalki, Abdulrahman L.; Hussein, Hussein K.; Khan, Jalal A. (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Bisphosphonates (BP) therapy is a vital option to reduce the risk of bone fracture in people who have osteoporosis. However, Bisphosphonate have displayed several side effects. Lepidium sativum (LS) plant and seeds has been used in traditional folk medicine as a mediator for bone fractures. Therefore, we aimed to compare the biochemical effects of LS alone (2% LS in diet, n=8), BP (Alendronate, 70 mg/kg s.c.; n=8) alone, or LS and BP combined in a rat model of glucocorticoid-induced osteoporosis (GIO) by injecting methylprednisolone 3.5 mg/kg per day for 4 weeks. Serum calcium (Ca), albumin, phosphorus (PO4), bone-specific alkaline phosphatase (b-ALP), and tartrate-resistant acid phosphatase (TRAP) were measured 4 weeks after induction of GIO. GIO-group showed significantly increased serum TRAP and decreased b-ALP. GIO-group also showed significantly decreased serum PO4 and unaltered Ca concentrations. Histological examination of GIO-group tibia bones indicates an osteoporotic changes and a concomitant decrease in percentage of trabecular area/bone marrow area (PTB) in the proximal femoral epiphysis. Treatment with either LS and/or BP ameliorated the above mentioned changes with variable degrees; with a net results of enhanced serum calcium, bone architecture, PTB, b-ALP and decreased TRAP in LS and LS+BP groups compared to that of animals treated with Alendronate alone. In conclusion, our findings present evidence supporting the potential benefits of LS in reducing the burden of GCs on bone health.